Enhancing Forgiveness in Bullying Victims: The Effectiveness of Self-Compassion Training Using Ho'oponopono Techniques - Mutmainna, Nurul; Murdiana, Sitti (Psikostudia : Jurnal Psikologi, 2024)
Bullying that occurs can affect individual mental health, namely stress, anxiety, difficulty socializing, trauma, depression, withdrawal and even suicide. This causes a feeling of revenge and has not forgiven all the bullying incidents that have occurred. The research design used a pretest-posttest control group design. This study aims to see the effectiveness of self-compassion through the hoponopono technique in increasing forgiveness in individual victims of bullying. Sampling was carried out using accidental sampling, the sample in this study amounted to 16 people who were divided into the experimental group and the control group. The instruments used were the multidimensional peer-victimization scale for participant screening and the heartland forgiveness scale.  The results of data analysis showed that the mean rank in the experimental group was 12.00 while in the control group the mean rank was 5.00. Asymp.Sig value. (1-tailed) of 0.002 indicates that p = 0.002 <0.05 which means that there is a significant difference in the level of forgiveness in the experimental group and the control group. The Wilcoxon test shows that the data values in the control group show the Asymp.Sig value. (2-tailed) shows 0.012 which means the p value <0.05 so that there are differences in the level of forgiveness before and after the hoponopono training. From the results of the data analysis, it can be concluded that self-compassion training through hoponopono can increase forgiveness in victims of bullying. Based on this, hoponopono can be applied in everyday life to increase forgiveness.Perundungan yang terjadi dapat berpengaruh terhadap kesehatan mental individu yaitu stress, kecemasan, sulit bersosialisasi, trauma, depresi, menarik diri bahkan hingga bunuh diri. Hal tersebut diakibatkan adanya dendam dan belum memaafkan seluruh peristiwa perundungan yang pernah terjadi. Penelitian ini bertujuan untuk melihat efektivitas self-compassion melaui teknik hoponopono terhadap peningkatan pemaafan pada individu korban perundungan. Penelitian ini merupakan penelitian eksperimen. Ada pun pengambilan sampel dilakukan dengan menggunakan accidental sampling, sampel pada penelitian ini berjumlah 16 orang yang dibagi kedalam kelompok eksperimen dan kelompok kontrol. Instrumen yang digunakan adalah multidimensional peer-victimization scale untuk skrining partisipan dan heartland forgiveness scale. Hasil analisis data menunjukkan bahwa kelompok eksperimen memiliki mean rank sebesar 12,00, sedangkan kelompok kontrol hanya 5,00. Nilai Asymp. Sig. (1-tailed) sebesar 0,002 (p = 0,002 < 0,05) menunjukkan adanya perbedaan signifikan dalam tingkat pemaafan antara kelompok eksperimen dan kelompok kontrol. Uji Wilcoxon pada kelompok kontrol menunjukkan nilai Asymp. Sig. (2-tailed) sebesar 0,012 (p < 0,05), yang berarti terdapat perbedaan signifikan dalam tingkat pemaafan sebelum dan sesudah pelatihan Ho'oponopono. Berdasarkan hasil tersebut, pelatihan self-compassion melalui Ho'oponopono terbukti efektif dalam meningkatkan pemaafan pada korban perundungan. Oleh karena itu, Ho'oponopono dapat diterapkan dalam kehidupan sehari-hari untuk meningkatkan kemampuan memaafkan.